A vaca leiteira e as mudanças climáticas globais - Baccari, Flávio [UNESP] (Malque Publishing, 2015)
High producing dairy cows are more sensitive to heat stress due mainly to their higher resting metabolic rate as compared to low producing and dry cows. Their responses to increasing levels of the temperature-humidity and the black globe-humidity indices are discussed as well as some aspects of heat tolerance as related to body temperature increase and milk production decrease. Some mitigation and adaptation practices are recommended to face the challenges of global climate changes.
The dairy cow and global climate changes
Keywords: Adaptation; Heat stress; Mitigation